Окремі аспекти закриття кримінального провадження у випадку відсутності складу кримінального правопорушення - Двойніков, О. О.; Dvoinikov, O. O.; Глобенко, Г. І.; Hlobenko, H. I. (Право і безпека. - 2014. - № 4 (55). - С. 98-102, 2014)
Розглянуто теоретичні та практичні проблеми, що виникають під час закриття слідчим, прокурором кримінального провадження у випадку встановлення відсутності складу кримінального правопорушення. Звернено увагу на недосконалість чинного Кримінального процесуального кодексу України у межах дослідженої проблеми, запропоновано доповнити ст. 3 чинного КПК України терміном «кримінальне правопорушення». Визначено перелік випадків, у яких практичним працівникам органів досудового розслідування. прокурору слід приймати рішення про закриття кримінального провадження на підставі п. 2 ч. 1 ст. 284 КПК України.

Considering the current criminal procedural legislation of Ukraine the theoretical and practical problems that arise during the closing of criminal proceedings by an investigator, prosecutor in cases of the absence of criminal offence’s corpus delicti are studied. Special attention is paid to the imperfection of the current Criminal Procedural Code within the studied problem, where there is no definition of «criminal offence» in its provisions. In order to eliminate this gap the author offered to amend the Art. 3 of the current Criminal Procedural Code of Ukraine with the term «criminal offence», which should be considered as guilty act (action or omission) according to the current law of Ukraine on criminal liability, which has a level of public danger typical for a crime or criminal offense and committed by a subject of criminal offence. It is suggested to determine criminal offence’s corpus delicti as a set of elements: object, objective side, subject, subjective side. Provisions of the Criminal Code of Ukraine and Criminal Procedural Code of Ukraine in this field are analyzed. Therefore, it is stated that practitioners of pre-trial investigation agencies should take the decision to close the criminal proceedings under the clause 2 section 1 of the Art. 284 of the Criminal Procedural Code of Ukraine in case of the absence of one or more elements of criminal offence’s corpus delicti in the action of a person; in case of establishing insignificance of committed act; in case of establishing circumstances precluding criminal nature specified in the Part VIII of the Criminal Code of Ukraine; in case of voluntary refusal of a person to stop criminal offence, when committed action does not contain another offence’s corpus delicti; in the case of the absence of the features of criminal offence’s special subject; in case of the absence in the action the features of repetition or systematic character, by which it is classified as a criminal offence. It is offered to amend the section 1 of the Art. 284 of the Criminal Procedural Code of Ukraine with the basis for closing criminal proceedings «in case of establishing circumstances that under the law of Ukraine on criminal liability admit the actions as legitimate ones».

Рассмотрены теоретические и практические проблемы, возникающие при прекращении следователем, прокурором уголовного производства в случае установления отсутствия состава уголовного правонарушения. Обращено внимание на несовершенство действующего Уголовного процессуального кодекса Украины в рамках исследованной проблемы, предложено дополнить ст. 3 действующего УПК Украины термином «уголовное правонарушение». Определён перечень случаев, в которых практическим работникам органов предварительного расследования, прокурору следует принимать решение о прекращении уголовного производства на основании п. 2 ч. 1 ст. 284 УПК Украины.
Some aspects of closing the criminal proceedings in case of the absence of criminal offence’s corpus delicti
Отдельные аспекты прекращения уголовного производства в случае отсутствия состава уголовного правонарушения
Keywords: закриття кримінального провадження; склад кримінального правопорушення; малозначність діяння; обставини, що виключають злочинність діяння; closure of criminal proceedings; criminal offence’s corpus delicti; insignificance of the act; circumstances precluding criminal nature; прекращение уголовного производства; состав уголовного правонарушения; малозначительность деяния; обстоятельства, исключающие преступность деяния